Factors Influencing the Satisfaction Level of Cultural Tourists in Malaysia - Lau Hui Xin,; R. Chandrashekar, (Research in Management of Technology and Business, 2023)
Cultural tourism is a rapidly expanding segment of the travel and tourist industry. Nothing defines and distinguishes a country more than its culture. Seeing a country's art, participating in its traditions, sampling its cuisine, and wandering through its history are without a doubt the best ways to learn about it. Thence, this study focuses on the purpose is to identifying the factors that influence cultural tourism on satisfaction with the level of cultural tourists in Malaysia. By using the quantitative method, 379 respondents will focus on inbound ASEAN and domestic tourists who visited Malacca have been chosen to answer the questionnaire. Statistical Package for Social Science (SPSS) will use to analyse the data. These results may serve as a reference to enhance the quality of the tourism sector in Malaysia.